To simplify the expression 3^3 x (2^-16)^4/3^6, we can start by evaluating the exponents.
First, let's simplify (2^-16)^4:
(2^-16)^4 = 2^(-16 * 4) = 2^-64
Next, let's simplify 3^3:
3^3 = 3^(3 * 1) = 3^3
Now that we have simplified the exponents, we can rewrite the expression as:
3^3 x 2^-64 / 3^6
Since the bases (3 and 2) are different, we cannot directly combine them. We will simplify each term separately:
3^3 = 3 * 3 * 3 = 27
2^-64 cannot be simplified further.
3^6 = 3 * 3 * 3 * 3 * 3 * 3 = 729
Now, we have:
27 x 2^-64 / 729
To simplify further, we can rewrite 2^-64 as (1/2)^64.
27 x (1/2)^64 / 729
Since 1/2 is the same as 2^-1, we can rewrite the expression as:
27 x (2^-1)^64 / 729
Using the property (a^m)^n = a^(m * n), we can simplify further:
27 x 2^(-1 * 64) / 729
27 x 2^-64 / 729
Now, we have:
27 / 729 x 2^-64
To simplify 27 / 729, we can notice that both numbers are divisible by 27:
27 / 729 = 1 / 27
So our expression becomes:
(1 / 27) x 2^-64
Now, we have simplified the original expression to (1 / 27) x 2^-64.
3^3 x (2^-16)^4/3^6
1 answer